Scaffolding Based Treffinger To Improve Students' Critical Thinking Skills - Triyanti, Putri Like; Noer, Sri Hastuti; Sutiarso, Sugeng (Journal of Education Reseach and Evaluation, 2021)
Critical thinking skills can encourage and develop students' learning to observe, find, and solve problems. Critical thinking skills can encourage and develop students' learning to observe, find, and solve problems. Thinking skills can be improved to improve the learning activities provided by the teacher. It is still challenging to improve critical thinking skills in student learning. Students tend to be passive in learning, often without the same thinking skills as the teacher, resulting in less development of critical thinking skills. The purpose of this study is to identify Treffinger-based scaffolding. This type of research is a meta-analysis. This article examines several international and national journals regarding Treffinger, Scaffolding, and critical thinking. The scientific studies included in this study were selected according to the criteria. This article is a study by several researchers regarding scaffolding and its effect on students' critical thinking skills and provides several recommendations for teachers and researchers regarding scaffolding and learning models. The result of the research is that scaffolding will be reduced or even eliminated in learning after students get a sufficient and correct understanding. Thus, Treffinger-based scaffolding can benefit students in critical thinking learning. Can Key Scaffolding help students solve problems and improve students' critical thinking skills. Treffinger's learning model can make students solve problems with ID and ideas chosen by students.